2022
DOI: 10.3390/vaccines10101693
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response to ChAdOx1 nCoV-19 (AZD1222) Vaccine in Kidney Transplant Recipients

Abstract: Kidney transplant recipients (KTRs) are at a much higher risk of complications and death following COVID-19 and are poor vaccine responders. The data are limited on the immune response to Covishield® in KTRs. We prospectively recruited a cohort of 67 KTRs aged >18 between April 2021 and December 2021. Each participant was given two intramuscular doses of Covishield®, each of 0.5 mL, at an interval of 12 weeks. A blood specimen of 5.0 mL was collected from each participant at two points within a few days bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…This study also showed a 4 fold rise in ASAb (9786 AU to 38,576 AU) titre after second dose of vaccine. We have previously reported a 36-fold rise in antibody titre after two doses in immunosuppressed renal transplant recipients [ 10 ]. As compared to those who did not have ASAb ( Table 3 ), the booster effect in participants with pre-existing ASAb showed peculiar features of marked booster effect after first dose without additional immune boosting after second dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also showed a 4 fold rise in ASAb (9786 AU to 38,576 AU) titre after second dose of vaccine. We have previously reported a 36-fold rise in antibody titre after two doses in immunosuppressed renal transplant recipients [ 10 ]. As compared to those who did not have ASAb ( Table 3 ), the booster effect in participants with pre-existing ASAb showed peculiar features of marked booster effect after first dose without additional immune boosting after second dose.…”
Section: Discussionmentioning
confidence: 99%
“…In India, this vaccine is manufactured by Serum Institute of India (Covishield ® ) and over 1.75 billion doses have been administered to date. The real-life data of Covishield ® shows promising results among HCWs, patients with liver cirrhosis [ 9 ], renal transplant recipients [ 10 ] and those on maintenance hemodialysis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The participants had received two doses of the vaccineat 13 weeks. 13,14 The 36 pairs of sera, collected after 11 weeks [5][6][7][8][9][10][11][12][13][14][15][16][17][18] of administration of second dose of the vaccine, were tested for ASAb and NAb. Following vaccination, 97% had ASAb and ASAb titer was 9405 (1635-25,000), whereas 83% of participants had NAb and NAb percentage was 96.4% (59.6-98.1%).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, high seroprevalence of ASAb has been observed in other group of unvaccinated populations such as health care workers, 16 people with cirrhosis, 17 or renal transplant recipients. 18 An Indian study from a quarantine facility in the state of Karnataka showed that 90% of the infection remains asymptomatic in the community. 19 Further, a high-quality systematic review of 350 studies suggested that nearly 35% of coronavirus infections remain asymptomatic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation